2021
DOI: 10.1016/j.visres.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Testing temporal integration of feature probability distributions using role-reversal effects in visual search

Abstract: The visual system is sensitive to statistical properties of complex scenes and can encode feature probability distributions in detail. This encoding could reflect a passive process due to the visual system's sensitivity to temporal perturbations in the input or a more active process of building probabilistic representations. To investigate this, we examined how observers temporally integrate two different orientation distributions from sequentially presented visual search trials. If the encoded probabilistic i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Many studies in the past two decades investigated the efficient nature of perceptual averaging from a set of items (see Introduction). While the main focus in this literature is rapid feature integration from the current trial to form a summary representation, only a few tested the influence of history and found contraction biases in mean estimation tasks for facial expressions ( Crawford et al, 2019 ), orientation ( Manassi et al, 2017 ; Son et al, 2021 ; Tanrikulu et al, 2021 ), and brightness ( Crawford et al, 2019 ). In these experiments, ensembles are presented all at once for a short time, but in real-world environments, groups of items are often dynamically perceived over longer time scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in the past two decades investigated the efficient nature of perceptual averaging from a set of items (see Introduction). While the main focus in this literature is rapid feature integration from the current trial to form a summary representation, only a few tested the influence of history and found contraction biases in mean estimation tasks for facial expressions ( Crawford et al, 2019 ), orientation ( Manassi et al, 2017 ; Son et al, 2021 ; Tanrikulu et al, 2021 ), and brightness ( Crawford et al, 2019 ). In these experiments, ensembles are presented all at once for a short time, but in real-world environments, groups of items are often dynamically perceived over longer time scales.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies describe the common attraction (positive) bias to recent stimuli (e.g., Cicchini et al, 2018 ; Fischer & Whitney, 2014 ; Liberman et al, 2018 ), others found it to be negative (i.e., a repulsion bias) under specific conditions ( Fritsche et al, 2017 ; Son et al, 2021 ). Serial dependence was also found to occur in ensemble statistics judgments with both attraction ( Manassi et al, 2017 ; Son et al, 2021 ; Suárez-Pinilla et al, 2018 ; Tanrıkulu et al, 2021 ) and repulsion ( Son et al, 2021 ; Suárez-Pinilla et al, 2018 ) biases by recently perceived ensembles, depending on different factors.…”
Section: Introductionmentioning
confidence: 90%
“…Strong visual cues have been noted to have the ability to skew memories of events, ascribing stronger relationships and recall (Tanrıkulu, Chetverikov, & Kristjánsson, 2021). The full moon is an overt phenomenon with known scientific influence such as gravitational pressures on tides and melatonin levels in humans (Hartstein et al, 2022).…”
Section: Research Backgroundmentioning
confidence: 99%